Will trust proceedings of the future be private?. Issue 9 (8th October 2019) - Alexander, Stephen
Abstract: This article considers the development, and future course, of the law of privacy in administrative trust proceedings. The author argues that the principles of open justice should remain as the starting point of judicial thinking; that this should mean that the courts' approach is driven by what is necessary to enable the public to see that justice is being administered fairly and impartially; and that the publication of details of parties and trusts in non-contentious trust proceedings is usually unlikely to help achieve that end. The author concludes that the issues of open justice and privacy are best balanced and accommodated by the policy, in administrative trust proceedings, of the court sitting in private and then issuing an anonymised judgment giving as much information as possible.